A quantitative study on the intention to use internet of things services - YILDIZ, Bülent; KÜTAHYALI, Dilber Nilay (Business Economics and Management Research Journal, 2023)
The Internet of Things (IoT) has become an integral part of our lives. It provides great convenience to consumers in their work and home lives and in the services they receive, such as health and tourism. However, as with other technological innovations, consumers have privacy and security concerns about IoT services. This study investigated how perceived usefulness and privacy risk affected consumers’ attitudes toward IoT services. The study also examined how their attitudes toward IoT services affected their intention to use them. The research hypotheses were tested with the structural equation model. The results showed that perceived usefulness positively affected consumers’ attitudes, affecting their intention to use IoT services. On the other hand, perceived privacy risk did not significantly affect their attitudes toward IoT services.
Keywords: İşletme; nesnelerin interneti; algılanan kullanışlılık; kullanım niyeti; internet of things; perceived usefulness; intention to use; Business Administration; 9. Industry and infrastructure